(untitled) (Diametros, 2019)
The colour incompatibility claim was first introduced by Wittgenstein in the Tractaus. It states that there can be only one colour in one place and time. It is commonly believed that Wittgenstein abandoned his conception of logical atomism after he had understood the consequences of his colour incompatibility claim. The main goal of this article is to provide an interpretation of the colour incompatibility claim in terms of Wittgenstein’s phenomenology. I will focus on two works which are of great significance for the colour incompatibility claim, namely, Some Remarks on Logical Form and Philosophical Remarks. The period between 1929 and 1930 is the time when these two works came into existence, and it is the beginning of the “middle period” of Wittgenstein’s philosophy. My attention will not only concern the fact that Wittgenstein formulated the colour incompatibility claim, but I will also address the issue of how this claim was justified. The grasp of Wittgenstein’s justification of the colour incompatibility claim will help to understand his phenomenology and his theory of philosophical grammar.